Pelatihan English Verbs untuk Siswa SMK Negeri 5 Palu - Said, Mawardin M; Rita, Ferry; Syafar, Anshari; Maghfira, Maghfira; Ibmasiah Wardatun Islamiyah; Mawardin, Ide Ilmiah; Mawardin, Ilmuislami (Universitas Negeri Surabaya, 2023)
This Community Service aims at training students in using English Verbs. They hopefully can increasevocabulary especially their English verbs so that they can make sentences and communicate in that foreign language. They are motivated to master English verbs used in their daily activities to be able to communicate inthat international language practically. Its speciic target is students having spirits to add English Verbsso thatthey can use them sustainably and influence their friends in using the English vocabulary in sentences. They easilycommunicate in the global language if have many its vocabularies. They also can be global learners.Communicative method is used to reach the objective. It is applied in interaction with the students. Its result isthe Training of English Verbs for the students has been gone on well. Practical Ways of Learning English wereexplained to them who were also trained to increase the vocabulary and use them in sentences so that they canpractice them even though have not veen fluent in making and expressing them. They hopefully master the EnglishVerbs since all English sentences must have verbs.